Effectiveness of cognitive behavior therapy and Reiki therapy on adolescents with depressive disorders inTehran, Iran - Charkhandeh, Mansoureh (2014)
Depression in childhood and adolescence is among the most common and disabling disorders. It is defined as a mood of sadness plus other emotional symptoms, such as low self-esteem, anhedonia, anxiety, guilt, pessimism, and loneliness. Depression disorders are assessed through structured clinical interviews and observation. Estimates of the prevalence of Major Depression Disorder (MDD) in adolescence range from 0.4% to 8.3% lifetime prevalence. Epidemiological studies from the literature on mental health of youth indicate that depression, drug abuse and suicide are among the three most common causes of death among young people. Some studies have been conducted to assess the state of mental health in Iran. The rate of attempted suicide among depressed patients in a community area is 0.5% in Iran, which is significantly lower than in the most recent clinical research. The aim of current research is to investigate the effectiveness of CBT and Reiki among depressed adolescents in Tehran, Iran. It is expected that using the CBT and Reiki approaches in the present study pioneers further work in this particular area of depression in children. Cognitive behavior therapy and Reiki are two non-pharmacological therapies. The purpose of the current study is to make a comparison between a psychotherapeutic approach (CBT) and an alternative medicine method (Reiki). Cognitive behavioral therapy is effective for mild childhood depression. Most anxiety and depression treatments include general skills-building strategies such as self-monitoring, psycho-education, problem-solving, social skills training, and reward plans thus; successful CBT would be expected to engender positive change in cognitive processing including decreasing negative automatic thoughts, maladaptive attitudes and assumptions, and decreased threat interpretations. Reiki is described by supporters as a holistic therapy which brings about healing on physical, emotional, mental and spiritual levels. It is classified as an alternative, complementary, or integrative method or therapy. This study involved a quantitative data collection method, with pre-test and post-test is design with two experimental groups and one control group. There were two periods of data collection for this study. The period one employed pre-test (T1) to assess depression score of participant by CDI, and the period two (T2) to measure depression score when two treatments (CBT and Reiki) are performed. One of the most common mental disorders in children and adolescents in Tehran is depression. These adolescents had been referred to psychotherapy clinics in different districts in Tehran. A multistage random sampling method was used in this study. A random sample was constructed by taking a series of simple random samples in different stages. The eligible adolescents referred to these health centers recruited for the study from June to September 2010. The following criteria were used to recruits participants: (a) aged 12-17, (b) met a minimum CDI score of 20, (c) met DSM-IV-TR criteria for major depression based on structural interview by two clinical psychologists, and (d) completed a pretreatment assessment. Each of the three treatment groups (CDI, Reiki, and the control group) included 80 samples, which provided an accumulated mixed gender total of 240 boys and girls. The number in the CBT group was reduced to 63 (34 girls and 29 boys). Reiki group therapy was performed for 65 depressed adolescents (34 girls and 31 boys). The number of samples in the control group at the end of treatment was 60 (33 girls and 27 boys). The data in this study were collected by a self-rating scale “Child Depression Inventory” (CDI) and backgrounds questionnaire. The CDI is a self-rating scale modeled on the Beck depression inventory (BDI) and adapted to young people 7-17 years of age. The depressive symptoms assessed include cognitive, affective, somatic and behavioral aspects. The 27 items were scored from 0 to 2. Clinical / categorical approach is proven that it covers symptoms of depression, most major and minor, according to the DSMIVTR. The CDI takes about 10-20 minutes to complete and contains five subscales: negative mood, interpersonal problems, ineffectiveness, anhedonia and negative selfesteem. The CDI was taken before start of treatment at the first stage to determine the level of depression score in adolescence (pre-test). At the second stage, the CDI was used after period of 12 sessions in Reiki and CBT treatments to determine depression score of the participants and to assess the effectiveness of the two methods on reduction of depression in adolescents (post-test). The CBT program was arranged in two sessions of one and a half hours per week. The planning totaled eighteens hours in twelve sessions over six weeks of the treatment period. Some of the treatment activities such as relaxation, discussion, solving of problems skills, and positive cognitive changes in CBT method were performed in groups. Reiki therapy was individually for 20 minutes in each session and two sessions in a week. The participants in a waitlist control group condition attended information sessions and were familiarized with the goals of the research. They were not receiving any treatment and education. Pearson Chi Square analysis to check any significant association although the demographic variables (gender, age, parental education, medical problems, living arrangements and family income) between there group (CBT, Reiki and control). Paired t-test was used to analyze the difference between pre-test and post-test in one group. One way ANOVA test and post-hoc test were used for analysis the difference between pre-test or post-test in three independent groups (CBT, Reiki and control). An independent t-test was also done to determine differences between posttest of male and female scores. The current study determined that CBT is an important independent variable in reducing of depression score of Iranian adolescents more than Reiki therapy. The CBT was same effect in decreasing depression scores of male and female while Reiki had different effect. The side results showed that CBT and Reiki programs led to reducing subscales scores (negative mood, interpersonal problems, ineffectiveness, anhedonia, negative self-esteem). Successful CBT treatment brings about positive changes in cognitive processing, including decreased negative automatic thoughts settings, and maladaptive assumptions and reduced threat interpretations. One of the most important findings from the quantitative data of this study is the number of participants who reported feeling relaxes during and after treatment. Some participants noted that the use of Reiki increases energy. Moreover, the CBT effects should help to solve these social and individual problems and it is recommended that counseling centers and the Iranian Ministry support both schools and other educational institutions, in helping to minimize if not solve the problem of mental disorders among Iranian youth. The practice of Reiki should be promoted and there should be efforts made to train Reiki masters. Reiki research should be encouraged and this traditional art of healing should be introduced to the scientific community. To control depression, there must be practical programs, such as relaxation, mediation, individual and group counseling, so they can support programs and help students and their abilities to deliver better services in the school.